Wadah dan Tanda Kubur, Sebuah Simbol dalam Tradisi Megalitik Masyarakat Nias Selatan - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2009)
AbstractIn relation to death, the burial is one of the procession of the human life cycle for every culture. Therefore, the procession of death have a very important role with the special treatment of the deceased. In relation to social life, the various aspects raised is a sign of the importance of the procession meant. To understand the various social aspects can be observed presumably conceived through the symbols on coffin and grave mark.